The Role of Teachers in Building Motivation for Learning Music through the Implementation of Interactive Learning Methods at SMP Negeri 3 Ungaran - Harfadme, Renada Aprilia; Aesijah, Siti (Riwayat: Educational Journal of History and Humanities, 2025)
The phenomenon observed at SMP Negeri 3 Ungaran indicates that music education faces challenges in maintaining students' interest and active engagement, particularly with the changes in learning styles and the integration of technology. The role of the teacher as a facilitator capable of creating an engaging and interactive learning environment is crucial in fostering students' exploration and deep understanding of music education content. This study examines the role of teachers and the implementation of interactive learning methods in music education at SMP Negeri 3 Ungaran, as well as the challenges related to changes in learning styles and the integration of technology. The study employs a descriptive qualitative approach. Data were collected through participatory observation, structured interviews with teachers, students, and the school principal, as well as documentation. Triangulation techniques were used to ensure data validity, which was then analyzed through stages of data collection, reduction, presentation, and conclusion drawing. The results of the study at SMP Negeri 3 Ungaran show that the role of teachers in building motivation for learning music is essential, particularly through the use of interactive learning methods. The application of methods such as group discussions, collaborative projects, and the use of digital media successfully increased students' motivation, engagement, and self-confidence. Students also demonstrated improvements in musical skills and social cooperation, particularly in ensemble learning with the xylophone and recorder.